2020
DOI: 10.1039/d0sm01536a
|View full text |Cite
|
Sign up to set email alerts
|

The hierarchical bulk molecular structure of poly(acrylamide) hydrogels: beyond the fishing net

Abstract: The polymeric structure of hydrogels is commonly presented in the literature as resembling a fishing net. However, this simple view cannot fully capture all the unique properties of these materials....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
5
28
0
Order By: Relevance
“…This is based on the estimate that for many natural porous media the length scale l is related to the permeability K by l 2 ≈ 10 2 K. For example, Cubaud & Ho (2004) find l 2 = 28.43K for square channels. This estimate of permeability and corresponding pore size appears reasonable, as Gombert et al (2020) report hierarchical structures in polyacrylamide hydrogels with features up to 100 nm size.…”
Section: Non-dimensionalisationsupporting
confidence: 76%
See 2 more Smart Citations
“…This is based on the estimate that for many natural porous media the length scale l is related to the permeability K by l 2 ≈ 10 2 K. For example, Cubaud & Ho (2004) find l 2 = 28.43K for square channels. This estimate of permeability and corresponding pore size appears reasonable, as Gombert et al (2020) report hierarchical structures in polyacrylamide hydrogels with features up to 100 nm size.…”
Section: Non-dimensionalisationsupporting
confidence: 76%
“…This estimate of permeability and corresponding pore size appears reasonable, as Gombert et al. (2020) report hierarchical structures in polyacrylamide hydrogels with features up to 100 nm size.…”
Section: One-dimensional Phenomenological Modelsupporting
confidence: 71%
See 1 more Smart Citation
“…The smallest structure consists of clusters of bis‐AAm with a size smaller than 4 nm, which agglomerate into domains that can grow to hundreds of nm and micron in size with increasing bis‐acrylamide concentration and are interconnected by polymer chains. [ 18 ] At the selected crosslinker concentration here (Table 1), that previous work observed clusters 100s of nm in size based on X‐ray scattering. We emphasize that these explicit domains are not clearly observed in free‐swelling PAAm hydrogels, perhaps due to the non‐uniform and large swelling, which made imaging challenging.…”
Section: Resultsmentioning
confidence: 96%
“…Recent work by Gombert et al. [ 18 ] has revealed that the difference between the polymerization kinetics of bis‐acrylamide and acrylamide leads to a hierarchical structure in PAAm hydrogels. The smallest structure consists of clusters of bis‐AAm with a size smaller than 4 nm, which agglomerate into domains that can grow to hundreds of nm and micron in size with increasing bis‐acrylamide concentration and are interconnected by polymer chains.…”
Section: Resultsmentioning
confidence: 99%